Zona pellucida birefringence and meiotic spindle visualization are not related to the time-lapse detected embryo morphokinetics in women with polycystic ovarian syndrome. (November 2018) - Tabibnejad, N.; Soleimani, M.; Aflatoonian, A.
Abstract: Objectives: Oocyte parameters as well as embryo developmental kinetics can be applied as non-invasive predictors for selection of viable embryos and clinical outcomes. Time-lapse morphokinetic events in conjunction with zona pellucida birefringence (ZPB) and meiotic spindle visualization (MSV) have been evaluated for predicting pregnancy outcome. Study design: We assessed a total of 547 embryos from 100 intra cytoplasmic sperm injection cycles in women with polycystic ovary syndrome (PCOS) and tubal factor infertility. ZPB and MSV were evaluated in 100 oocytes using polarized microscope. Time-lapse archives were noted for time to pronuclear fading (tPNf), time to 2–8 cells (t2–t8), direct cleavage, reverse cleavage and also for the presence of multinucleation. Results: The mean timings of embryo morphokinetics were not significantly different between high and low ZPB and visible and not-visible meiotic spindle oocytes in the PCOS group (P > 0.05). Furthermore implantation rate was 4.6 fold higher in embryos derived from oocytes with visible meiotic spindles compared to those without visible meiotic spindle in PCOS patients (P < 0.05). We observed that chemical and clinical pregnancy rates as well as live birth were higher in transferred embryos which formed from oocytes with visible meiotic spindle (27.6% vs.16.7%), (24.1% vs. 8.3%) and (24.1% vs. 8.3%) respectively. According to logistic regression analysis, only tPNf significantly influenced clinical pregnancy and live birth ( P  < 0.05). Conclusion: Time-lapse embryo parameters are not related to oocyte ZPB and MSV status. However, clinical pregnancy and live birth have been affected by the presence of meiotic spindle.